Pengaruh Tangible, Emphaty, Responsiveness, Assurance, Dan Reliability Terhadap Loyalitas Pelanggan Pada Hotel Bunda Padang - Lidya Martha; Risky Jordan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research was conducted to determine the effect of Tangible, Empathy, Responsiveness, Assurance and Reliability on Customer Loyalty at Bunda Padang Hotel. The population in this study were guests at the Bunda Padang Hotel, totaling 210 respondents using the Total Sampling technique. Total sampling is a sampling technique when all members of the population are used as samples. Research data were collected from respondents’ results and analyzed by multiple linear regression, hypothesis testing and F test hypothesis testing of all variables simultaneously, it can be concluded that the Tangible variable has a positive and significant effect on Loyalty at Bunda Padang Hotel. Empathy variable has a positive and significant effect on Customer Loyalty at Bunda Padang Hotel. The Responsiveness variable has a positive and significant effect on Customer Loyalty at the Bunda Padang Hotel. Assurance variable has no positive and significant effect on Customer Loyalty at Bunda Padang Hotel. The reliability variable has no positive and significant effect on customer loyalty at Bunda Padang Hotel. Simultaneous calculation results show a significance of 0.000 <0.05 probability, so that there is a positive and significant effect of Tangible, Empathy, Responsiveness, Assurance and Reliability on Customer Loyalty at Bunda Padang Hotel together.